E-Learning Flipped Classroom: Instituting an Integrated Islamic Education Paradigm for Character Building - Lailial Muhtifah; Erwin Mahrus; Nur Rahmiani (Nazhruna: Jurnal Pendidikan Islam, 2022)
Islamic education today has faced very complex challenges. The endless pandemic, the era of the Industrial Revolution 4.0, and even Society 5.0 are among the challenges that must be well responded. Therefore, a paradigm shift is a must in Islamic Education today. This work offers an exploration of the need to institutionalize a new paradigm of integrative Islamic education through e-learning flipped classroom (ELFC). This study is library research using literature as the basis for extracting data. This study uses a qualitative approach with the method of documentation. The purpose of this research is exploratory, namely finding the concept of a new paradigm of integrative Islamic education through ELFC in developing the character of Mukmin Ulul Albab in the field of Islamic Education. This study concludes that the new paradigm of Islamic Education which is integrative, effective, and efficient, along very urgent to be institutionalized in Islamic Educational Institutions. The steps of institutionalization through institutional design are as follows: preparation of regulations, procedures, values, and organizational structures to direct appropriate behaviour because of mutual agreement in the form of regulations and or institutional policies. The findings of this concept have implications for character growth into spirituality, moral nobility, breadth of knowledge, and professional maturity. These implications become very important because alumni who are able to take part in global scope but still manifest their identity as the true believers are the success of Islamic Education.